2005
DOI: 10.1073/pnas.0502035102
|View full text |Cite
|
Sign up to set email alerts
|

Examining bacterial species under the specter of gene transfer and exchange

Abstract: Even in lieu of a dependable species concept for asexual organisms, the classification of bacteria into discrete taxonomic units is considered to be obstructed by the potential for lateral gene transfer (LGT) among lineages at virtually all phylogenetic levels. In most bacterial genomes, large proportions of genes are introduced by LGT, as indicated by their compositional features and͞or phylogenetic distributions, and there is also clear evidence of LGT between very distantly related organisms. By adopting a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
147
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(154 citation statements)
references
References 45 publications
5
147
0
1
Order By: Relevance
“…In fact, recent analysis of protein families suggests that HGT, and not gene duplication, has driven protein expansion and functional novelty in bacteria, which is in contrast with most eukaryotic organisms (Treangen and Rocha, 2011). Sequencing of thousands of microbial genomes during the past two decades has allowed the identification of HGT events at different timescales, from ancestral to recent events, and between organisms of varied evolutionary relatedness, from closely related genomes to very distantly related ones (Gogarten et al, 2002;Beiko et al, 2005;Ochman et al, 2005;Zhaxybayeva et al, 2009a), revealing that HGT has affected the evolutionary history of most, if not all, bacterial lineages.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent analysis of protein families suggests that HGT, and not gene duplication, has driven protein expansion and functional novelty in bacteria, which is in contrast with most eukaryotic organisms (Treangen and Rocha, 2011). Sequencing of thousands of microbial genomes during the past two decades has allowed the identification of HGT events at different timescales, from ancestral to recent events, and between organisms of varied evolutionary relatedness, from closely related genomes to very distantly related ones (Gogarten et al, 2002;Beiko et al, 2005;Ochman et al, 2005;Zhaxybayeva et al, 2009a), revealing that HGT has affected the evolutionary history of most, if not all, bacterial lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Ochman et al (2005) analysed HGT at the shallower taxonomic levels and concluded that while there was relatively frequent HGT between homologous genes within species, there was a much lower amount of HGT between homologues across the species boundary. Given that new genomes are being sequenced on a daily basis, we can examine what this structure means for microbiology.…”
Section: Introductionmentioning
confidence: 99%
“…Homologous recombination, according to Ochman et al (2005), occurs mainly within a bacterial species, but there is very little recombination (approx. 1%) between any given species and its close relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the established notion of parent to offspring inheritance of genes and functions, HGT enables the direct transfer between individuals of the same generation, and, more importantly, across species boundaries (Ochman et al, 2005;Daubin & Szöllősi, 2016). Bacteria have at least three commonly known mechanisms for this transfer (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%